1993
DOI: 10.1016/0014-5793(93)81494-k
|View full text |Cite
|
Sign up to set email alerts
|

Human amnion epithelial cells assemble tenascins and three fibronectin isoforms in the extracellular matrix

Abstract: Monoclonalantibodies (MAb) were used to show that cultured human amnion epithelial (HuA) cells produce tenascins (Tn) and isoforms of cellular fibronectin (cFn). Tn polypeptides of M, 280,000 and 190,000, assembled into extracellular matrix (ECM) but not secreted into the culture medium by HuA cells, were electrophoretically similar to those produced by human fibroblasts as revealed with domain-specific MAbs. The results suggested that most Fn produced by HuA cells contained the extradomain (ED) A and an oncof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Maternal vascular endothelial damage plays a critical role in the development of preeclampsia (16). Because plasma fibronectin is a marker of endothelial damage (5,21), total or cellular fibronectin determinations have been used to differentiate normal and preeclamptic pregnancies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In our study, we evaluated ED-B fibronectin, an isoform of fibronectin, which is synthesized in the endothelium of blood vessels and released to the extracellular space at sites of vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal vascular endothelial damage plays a critical role in the development of preeclampsia (16). Because plasma fibronectin is a marker of endothelial damage (5,21), total or cellular fibronectin determinations have been used to differentiate normal and preeclamptic pregnancies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In our study, we evaluated ED-B fibronectin, an isoform of fibronectin, which is synthesized in the endothelium of blood vessels and released to the extracellular space at sites of vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen types I, III, IV, V and VII, laminin (Fig. 2D), and fibronectin have been identified in the amniotic BM [53,54,[63][64][65]. Fukuda Fig.…”
Section: Extracellular Matrix Components Mesenchymementioning
confidence: 99%
“…It has been reported that human amnion epithelial cells secrete cellular (III-A domain containing) and oncofetal (III-B containing) fibronectin isoforms that are assembled in the extracellular matrix [21]. Fibronectins in the amniotic basal lamina, particularly oncofetal isoform, is a part of healing process in this tissue due to the rapidly growing fetus causing partly shears in the amnion [22].…”
Section: Discussionmentioning
confidence: 99%